2009
DOI: 10.1111/j.1600-0587.2008.05591.x
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of temperate and tropical stream fish assemblages

Abstract: The hypothesis of convergence takes the deterministic view that community (or assemblage) structure can be predicted from the environment, and that the environment is expected to drive evolution in a predictable direction. Here we present results of a comparative study of freshwater fish assemblages from headwater streams in four continents (Europe, North America, Africa and South America), with the general objective of testing whether these assemblages display convergent structures under comparable environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
91
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(104 citation statements)
references
References 64 publications
10
91
1
1
Order By: Relevance
“…Therefore, we expect lower richness and higher dependence of allochthonous input in headwaters when compared to downstream waters (Vannote et al, 1980). In fact, more complex stretches presented higher richness in the study, which was also reported by several studies (Viana, 1989;Aquino, 2008;Hitt & Angermeier, 2008;Ibañez et al, 2009). Through the CCA, variables that more influenced species distribution patterns in the APA were related directly or indirectly to the water volume and habitats complexity.…”
Section: Discussionsupporting
confidence: 67%
“…Therefore, we expect lower richness and higher dependence of allochthonous input in headwaters when compared to downstream waters (Vannote et al, 1980). In fact, more complex stretches presented higher richness in the study, which was also reported by several studies (Viana, 1989;Aquino, 2008;Hitt & Angermeier, 2008;Ibañez et al, 2009). Through the CCA, variables that more influenced species distribution patterns in the APA were related directly or indirectly to the water volume and habitats complexity.…”
Section: Discussionsupporting
confidence: 67%
“…Indeed, we found that the environment explained a higher proportion of the variation in trophic structure than in species abundance. These results concur with studies carried out in large spatial scales (Hoeinghaus et al, 2007;Ibañez et al, 2009;Cunico et al, 2011) and show that assemblages in environmentally similar conditions must have high similarity in trophic composition, even if the taxonomic composition is different. In our case, different species, sharing the same diet, replace each other in environmentally similar riffles, reason by which the variation on the diet-related traits at community level were more predictable.…”
Section: Discussionsupporting
confidence: 81%
“…In fact, increasing local species richness along the longitudinal stream gradient is a very well known pattern (e.g. Oberdorff et al, 1995;Pont et al, 1995;Grenouillet et al, 2004) that has been observed on almost all continents (Ibañez et al, 2009). As expected, the well oxygenated, summer-cold rhithral and small permanent upland basins (e.g.…”
Section: Figurementioning
confidence: 62%
“…The complementary use of both taxonomic and functional traits of fish assemblages was fundamental to interpret these results. The composition of traits in lotic fish communities appears to be structured along an environmental gradient (Pont et al, 2006Hoeinghaus et al, 2007;Ibañez et al, 2007Ibañez et al, , 2009Logez et al, 2010), whereas patterns derived from taxonomic composition reflect the role played by geographical and historical factors in species distribution (Hoeinghaus et al, 2007). From North to South, and expressing an altitude and climate gradient, fish-regions related to the morphoclimatic regions (the base of abiotic typology) (Figures 1 and 6).…”
Section: Figurementioning
confidence: 99%